SELF-CALIBRATION OF ULTRASONIC TRANSDUCERS IN AN INTELLIGENT DATA ACQUISITION SYSTEM - Papageorgiou, Chris; Laopoulos, Theodore (International Journal of Computing, 2014)
The rapid growth of powerful single-chip microcomputers for monitoring and data acquisition applications permits nowadays the design of advanced measuring systems. The work reported here is presenting an advanced on-line monitoring configuration in order to improve the performance and extend the lifetime of ultrasonic transducers by applying an automated testing and calibration technique. The operation of this instrumentation system is based on the fast measurement of frequency and amplitude, performed by the proposed configuration. The combination of this information with the time of flight of each pulse-train is then used to derive practically all characteristics of ultrasonic transducers. Due to its low cost and small size, the system can be used either for characterization and classification of transducers, or as a self-testing and automated calibration section within any high performance ultrasonic system.